ANALISIS BIAYA PRODUKSI ES BALOK PADA PROFITABILITAS PENJUALAN PT PERIKANAN NUSANTARA (PERSERO) CABANG SORONG - Yerrynaldo Loppies (Manis: Jurnal Manajemen dan Bisnis, 2019)
The profitability of sales is one of the main goals of companies to measureperformance leadership or management in other words efficiency andeffectiveness of companies.The cost of my ingredients, how long it will last, and the cost of the factory headmust be calculated quickly. Especially the overheads factory which is oftenoverlooked in production calculations. In addition to the cost of the material andthe cost of the process, the costs include the cost of overhead mill electricity, thecost of shrinking, the cost of repairing the machine, and the maintenance of themachine. All costs must be calculated quickly because they affect the profitabilityof sales.This research took place at Jalan General Ahmad Yani Sorong No. 24 byusing a method of costing in establishing the profitability of the seller and usingthe deposit policy for the main factory price in the overhead charge that is chargedto each product.Based on the results of a comparative data analysis, the method of thecompany with the full costing method has different results in the profitability ofsales.